The application of rapid prototyping technology and FMEA quality tool in the development of automotive component - Wan Yusoff, Wan Ahmad Yusmawiza; Sa’edun, Mohamad; Afiq, Faidhi (2009)
The purpose of this research is to study and apply the rapid prototyping technique using fused deposition modeling (FDM) in improving the quality of an automotive part. A machine that works under FDM principle will be used to produce the final product. An automotive component has been selected as the product for this research and application. Before continuing the fabrication of product, the critical path that must be considered is the design improvement to the target product. Failure mode effect analysis (FMEA) introduced as a tool in to improve the quality design to a better product level. The analysis from FMEA tool is translated to the design and product development. The research's findings however focus to only a selected part in automotive component. This result is inapplicable to other automotive component. Selection of material for fabrication limited to the machine availability and ability. This is the first known research that adopts a FDM machine to improve the existing product without ignoring the product functionality in real condition.